An Empirical Study on Forex Risk Management Strategies - Dash, Mihir; Babu, Narendra; Kodagi, Mahesh; B. Y., Vivekanand (Indian Journal of Finance, 2008)
In the world of globalization and international business, firms would be performing one or the other kind of international activity like selling its products abroad, sourcing its raw materials from abroad, raising funds abroad or investing in international markets, and would have to deal with many currencies for making or receiving payments. This would expose them to foreign exchange risk, where an appreciation or depreciation of the currency it is dealing with may eat away its profits, making it necessary to manage foreign exchange risk.